PENYEMBUHAN LUKA DECUBITUS PADA TIKUS PUTIH - Moch. Agus Krisno Budiyanto (Universitas Muhammadiyah Malang, 2011)
Chronic wounds are still problem is one of the most frequent among the community. Pressure ulcers (decubitus) are examples of types of chronic wounds in which the maintenance costs of the injury fairly expensive. The use of plants is an appropriate alternative for the treatment of decubitus chronic wounds. One among the many plants that are known efficacious drugs for the health of Aloe vera. With the various components contained therein, aloe vera is known to affect the decubitus chronic wound healing. This study is purely experimental posttest-only design approach. The sample uses a white rats strain wistar female, weight 150-250 gr and 2,5 to 3 months of age. The variable is the concentration of the extract of Aloe vera and scores healing pressure ulcers (decubitus) degree II in white rats. The data obtained using observation, then analyzed with the assumption test (Lilliefors test and the Barlett test), one way Anova test and different test real distance of Duncan with significansy values of 0,05. The results indicate that there is the influence of various concentrations of leaf extract of Aloe vera to diameter decubitus chronic wound healing in rats and the concentration of leaf extract of Aloe vera 100% to give a good effect on the diameter of decubitus chronic wound healing on white rats (á 0.05).